Faktor-Faktor yang mempengaruhi Minat Wakaf Masyarakat di Kota Lhokseumawe - Falahuddin, Falahuddin; Fuadi, Fuadi; Ramadhan, Muhammad Rizki (Jurnal EMT KITA, 2019)
This research is to find out the factors that influence the community Waqf Interest in Lhokseumawe City. The data used are primary data with a sample of 100 respondents. The data analysis method uses multiple linear regression with OLS (Ordinary Least Square) method. The results showed that community religious knowledge had a positive and not significant effect on waqf interest in Lhokseumawe. Perception of Waqf has a positive and insignificant effect on community Waqf Interest in Lhokseumawe City, and Revenue has a positive and insignificant effect on Waqf Community Interest in Lhokseumawe City. The determination test results used were 4%.Â Keywords: Wakaf Interests, Religiosity Knowledge, Wakif Perception, Income.